2018
DOI: 10.3389/fimmu.2018.00375
|View full text |Cite
|
Sign up to set email alerts
|

Making Thymus Visible: Understanding T-Cell Development from a New Perspective

Abstract: T-cell development is coupled with a highly ordered migratory pattern. Lymphoid progenitors must follow a precise journey; starting from the hematopoietic tissue, they move toward the thymus and then migrate into and out of distinct thymic microenvironments, where they receive signals and cues required for their differentiation into naïve T-cells. Knowing where, when, and how these cells make directional “decisions” is key to understanding T-cell development. Such insights can be gained by directly observing d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 66 publications
0
20
0
Order By: Relevance
“…Zebrafish may prove a useful model for addressing this question. The developmental origin, anatomical location and genetics underlying the development of adaptive immunity are largely conserved between zebrafish and mammals [241][242][243][244][245][246]. In recent years, studies of zebrafish lymphocytes have also revealed the existence of functionally conserved mature T cell subsets, such as CD4 + helper T cells [247,248], T regulatory cells [247,249,250] and γδ T cells [251].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Zebrafish may prove a useful model for addressing this question. The developmental origin, anatomical location and genetics underlying the development of adaptive immunity are largely conserved between zebrafish and mammals [241][242][243][244][245][246]. In recent years, studies of zebrafish lymphocytes have also revealed the existence of functionally conserved mature T cell subsets, such as CD4 + helper T cells [247,248], T regulatory cells [247,249,250] and γδ T cells [251].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…To prevent the kidney from returning to its original position, improved methods suggest closing the lateral sides of the skin incision with stitches (Caetano et al, 2012). Although the transplanted thymus approach has been successfully used in various studies, limitations of this approach include the complexity of the surgery required for transplantation, and the fact that different corporal conditions exist in the surrounding environment of a thymus transplanted in the kidney as opposed to a thymus located in the thoracic cavity (Aghaallaei & Bajoghli, 2018). Ex vivo alternatives to the complex transplantation procedure include extraction of individual thymic lobes perfused with oxygenated medium, followed by imaging by two photon microscopy , and imaging thymic slices Pérez et al, 2007;Savino et al, 1989), Plasmodium spp., Francelin et al, 2011;Gameiro et al, 2010) and T. gondii (Huldt et al 1973;Kugler et al, 2016;…”
Section: Methods For Ivm-based Visualization Of the Thymusmentioning
confidence: 99%
“…T cell development starts when T cell precursors migrate from the bone marrow or the fetal liver to the thymus. 1 In the thymic microenvironment, these precursor cells undergo a series of differentiation and selection events in different regions of the thymus, resulting in a diverse repertoire of mature T cells to establish immune protection against foreign antigens and immune tolerance toward self-antigens. 2 This process happens prenatally and involves several cell types including thymic epithelial cells and dendritic cells (DCs).…”
mentioning
confidence: 99%
“…2 This process happens prenatally and involves several cell types including thymic epithelial cells and dendritic cells (DCs). 1 Recent development of single-cell RNA seq (scRNA-seq) technology has allowed precise mapping of different cell types and trajectories of organ development. 3 Indeed, single-cell RNA sequencing (scRNA-seq) has revealed details of murine T cell development and thymic composition 4 ; however, human T cell development is vastly distinct from other animals.…”
mentioning
confidence: 99%
See 1 more Smart Citation